'Transitory urbanism' for the creative industries in a top-down regeneration process (Nantes, France). Issue 10 (3rd October 2022) - Darchen, Sébastien; Simon, Gwendal
ABSTRACT: This article studies the low-cost strategy associated with the provision of temporary spaces for start-up companies in the 'Quartier de la Création', a project within the large regeneration scheme: Ile de Nantes. The method, 'transitory urbanism', combines urban redevelopment and economic development strategies. We analyse the factors enabling the implementation of this method in practice. We argue that this method illustrates a regeneration strategy – with its limits – slightly different from the three types listed in typology on brownfield regeneration strategies. As 'transitory urbanism' happens within a top-down regeneration process, our findings complement the existing literature on planning contexts related to 'Cultural Brownfields' in Europe and specifically on 'transitory urbanism' as a method. The data collection is based on semi-structured interviews with stakeholders involved in the regeneration process as well as quantitative data collected on the number of jobs in temporary spaces for creative industries. Our main findings is that 'transitory urbanism' relies on three main conditions: (1) The SPL status of the redevelopment agency SAMOA; (2) The 'Precarious Occupation Agreement'; (3) A combination of financing mechanisms that we explain in detail.